STUDI DESKRIPTIF TENTANG MOTIVASI BELAJAR SISWA SMP MUHAMMADIYAH AL-KAUTSAR PK KARTASURA PADA EKSTRAKURIKULER TAPAK SUCI - Muttaqien, Sajid Dzakwan; Jariono, Gatot; Sudarmanto, Eko; Nurhidayat, Nurhidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the learning motivation of students at Muhammadiyah Al-Kautsar PK Junior High School in Kartasura in participating in the Tapak Suci extracurricular activity. The study employed a quantitative approach using a descriptive method. The study population consisted of all eighth-grade students participating in the Tapak Suci extracurricular activity, with a sample of 33 students selected using purposive sampling. Data collection was conducted using a questionnaire consisting of 20 statements based on a five-point Likert scale, covering indicators of internal and external factors of learning motivation. The data were analyzed using descriptive statistical techniques. The results indicate that students’ learning motivation falls into the “very high” category, with an average score of 87.79. A total of 23 students (69.70%) were in the “very high” category, and 10 students (30.30%) were in the “high” category. All indicators—both internal and external factors—fell into the “very high” category. Coach support was the highest-scoring indicator, followed by the need to achieve and peer support. It was concluded that the nature of Tapak Suci activities—which combine sports, martial arts, character building, and Islamic values—contributes significantly to building students’ learning motivation.